CircUCK2(2,3) promotes cancer progression and enhances synergistic cytotoxicity of lenvatinib with EGFR inhibitors via activating CNIH4–TGFα–EGFR signaling - Xindong Wei; Anfeng Si; Shuai Zhao; Yi Fu; Jilei Li; Kedeerya Aishanjiang; Yujie Ma; Chang Yu; Bo Yu; Chunhong Cui; Hui Wang; Xianming Kong; et al. (Cellular & Molecular Biology Letters)
Abstract Background Circular (circ)RNAs have emerged as crucial contributors to cancer progression. Nonetheless, the expression regulation, biological functions, and underlying mechanisms of circRNAs in mediating hepatocellular carcinoma (HCC) progression remain insufficiently elucidated. Methods We identified circUCK2(2,3) through circRNA sequencing, RT–PCR, and Sanger sequencing. CircUCK2(2,3) levels were measured in two independent HCC cohorts using quantitative real-time PCR (qRT–PCR). We explored the functions of circUCK2(2,3) using gain- and loss-of-function assays. Techniques such as RNA-sequencing, RNA immunoprecipitation (RIP), polysome fractionation, RNA pulldown, dual luciferase reporter assay, inhibitors of EGFR downstream signaling, CRISPR–Cas9, and medium transfer assays were employed to investigate the regulatory mechanisms and the protumoral activities of circUCK2(2,3). Additionally, in vitro cytotoxic assays and patient-derived xenograft (PDX) models assessed the effects of circUCK2(2,3) on the cytotoxic synergy of lenvatinib and EGFR inhibitors. Results CircUCK2(2,3) is upregulated in HCC tissues and serves as an independent risk factor for poor recurrence-free survival. The expression of circUCK2(2,3) is independent on its host gene, UCK2, but is regulated by its upstream promoter and flanking inverted complementary sequences. Functionally, circUCK2(2,3) enhances HCC proliferation, migration, and invasion, both in vitro and in vivo. Mechanistically, by sponging miR-149-5p, circUCK2(2,3) increases CNIH4 levels, which in turn amplifies TGFα secretion, resulting in the activation of EGFR and downstream pAKT and pERK signaling pathways. Moreover, circUCK2(2,3) overexpression sensitizes HCC cells to EGFR inhibitors, and increases the synergistic cytotoxicity of combined lenvatinib and EGFR inhibitor treatment. Conclusions CircUCK2(2,3) regulates a novel oncogenic pathway, miR-149-5p–CNIH4–TGFα–EGFR, in HCC, presenting a viable therapeutic target and biomarker for the precision treatment of HCC. Graphical Abstract